Synthesis, characterization and melt spinning of a block copolymer of L-lactide and ε-caprolactone for potential use as an absorbable monofilament surgical suture - Baimark Y. (2014)
This paper describes the synthesis and characterization of a block copolymer of L-lactide (LL) and ε-caprolactone (CL) and its subsequent melt spinning into a monofilament fiber. The synthesis reaction was a two-step process. In the first step, an approximately 50:50 mol% random copolymer, P(LL-co-CL), was synthesized via bulk copolymerization of LL and CL. This first-step prepolymer then became the macroinitiator in the second-step reaction in which more LL monomer was added to form a block copolymer, PLL-b-P(LL-co-CL)-b-PLL. Both the prepolymer and block copolymer were characterized by a combination of analytical techniques comprising dilute-solution viscometry, GPC, 1H and 13C NMR, DSC and TG. The block copolymer was then processed into a monofilament fiber using a small-scale melt spinning apparatus. The fiber was spun with a minimum amount of chain orientation and crystallinity so that its semi-crystalline morphology could be constructed under more controlled conditions in subsequent off-line hot-drawing and annealing steps. In this way, the fiber's tensile properties and dimensional stability were developed, as indicated by the changes in its stress-strain curve. The final drawn and annealed fiber had a tensile strength (> 400 MPa) approaching that of a commercial PDS II suture of similar size. It is considered that this type of block copolymer has the potential to be developed further as a lower-cost alternative to the current commercial monofilament surgical sutures. © 2005 Springer Science + Business Media, Inc.